Hubungan Strategi Coping, Dukungan Keluarga dan Dukungan Bidan Terhadap Kecemasan Primigravida Menghadapi Persalinan di PMB Ambarwati Kabupaten Sintang - Arum Seftiani Lestari; Dian Ika Pratiwi; Atri Rudtitasari; Paskalia Tri Kurniati; Yunida Haryanti; Rizki Amartani; Miftah Chairunnisa (Jurnal Medika Nusantara, 2024)
Any woman who is pregnant will feel anxiety and concerns when faced with her delivery the first pregnacy. This is caused by lack of experience and the fear of high risk during childbirth. The purpose of this study was to determine the relationship betwen coping strategies, family support and midwife with anxiety during delivery among mother with first pregnancy in PMB Ambarwati. This study used a descriptive analytical method with cross sectional approach. The sample of 32 respondents. The sampling technique used total sampling. The result show that a significant relationship between coping strategies anxiety during delivery among mother with first pregnancy Pvalue = 0,018 (OR= 8. 95% CI 1,5-42,5). There is a significant relationship between family support anxiety during delivery among mother with first pregnancy with Pvalue = 0,001 (OR= 25. 95% CI 3,5-182). There is a significant relationship between midwife support anxiety during delivery among mother with first pregnancy Pvalue = 0,049 (OR= 6. 95% CI 1,2-32,3). Suggestion research is for PMB Ambarwati provided advice on preparing for childbirth in order to minimize the occurence of anxiety.